2020
DOI: 10.14198/jhse.2021.163.09
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of motivation towards sports practice in students of Primary Education in Galicia. A descriptive study

Abstract: The current technological revolution has benefited the development of the human being. However, sedentary lifestyle has increased, and consequently, health problems, such as childhood obesity. The combination of physical activity with appropriate educational strategies are the most effective tools to fight against childhood obesity. But it is necessary to take into account the motivation towards the practice of physical exercise to generate the necessary adherence to generate healthy lifestyles and increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Regarding possible differences by gender, it is observed in Table 3 that there are significant differences in the intrinsic, identified and external dimensions with p-values < 0.01. In the case of intrinsic motivation, males present higher values than females, a fact already advanced by Mecías et al when they proposed that 5th and 6th grade male students showed more motivation than girls towards physical activity [31]. Higher scores were also obtained from males in identified motivation, especially in external motivation, where the males tend to be more concerned with being superior in order to meet with people's approval.…”
Section: Discussionmentioning
confidence: 85%
“…Regarding possible differences by gender, it is observed in Table 3 that there are significant differences in the intrinsic, identified and external dimensions with p-values < 0.01. In the case of intrinsic motivation, males present higher values than females, a fact already advanced by Mecías et al when they proposed that 5th and 6th grade male students showed more motivation than girls towards physical activity [31]. Higher scores were also obtained from males in identified motivation, especially in external motivation, where the males tend to be more concerned with being superior in order to meet with people's approval.…”
Section: Discussionmentioning
confidence: 85%
“…These programs in primary schools, based on cooking classes, health education, and work on eating disorders, have been shown to be effective in changing the behaviour of school-age children, making the school the best setting to intervene and decrease childhood obesity rates [20,21]. On the other hand, strategies and programs focused on increasing levels of physical activity both inside and outside the school context should favor or develop an increase in the enjoyment of the physical activity carried out and the appearance of feelings of self-efficacy [22][23][24][25]. Active recesses, active learning in the classroom, and complementary activities related to physical activity or activities that require the participation of the educational community, have also confirmed an increase in levels of physical activity in non-teaching moments and in the leisure time of schoolchildren [15,26].…”
Section: Introductionmentioning
confidence: 99%